Pengaruh Health Education Vulva Hygiene Dengan Audio Visual Dan Media Cetak (Booklet) Terhadap Pengetahuan Tentang Fluor Albus Pada Remaja di Pondok Pesantren Al Muhajirin 2 Tambakberas Jombang - Eka Sofia Larasati; Erna Ts; Faishol Roni; Leo Yosdimyati; Tiara Fatma Pratiwi (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2024)
Abstract Vaginal discharge is one of the reproductive health problems experienced by young women. the causes and prevention of vaginal discharge which, if not treated properly, can be fatal.This study aims to determine the effect of health education on vulva hygiene using audiovisual and print media on knowledge about preventing fluoride in adolescents at Pondok Al Muhajirin 2 Tambakberas Jombang. The type of research used was pre-experimental using a